Computer-graphic facial reconstruction - Clement, Hohn G. (Elsevier academic press, 2005)
This unique books looks at a cost-efficient, fast and accurate means of facial reconstruction--from segmented, decomposed, or skeletal remains--using computer-graphic and computational means. Computer-Graphic Facial Reconstruction is designed as a valuable resource for those scientists designing new research projects and protocols, as well as a practical handbook of methods and techniques for medico-legal practitioners who actually identify the faceless victims of crime. It looks at a variety of approaches: artificial intelligence using neural networks, case-based reasoning, Baysian belief systems, along with a variety of imaging methods: radiological, CT, MRI and the use of imaging devices.